2010
DOI: 10.5603/arm.27709
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Fibrosis and Inflammation in Exhaled Breath Condensate (EBC) and Bronchoalveolar Lavage Fluid (BALF) of Patients with Pulmonary Sarcoidosis: A Pilot Study

Abstract: Introduction: Sarcoidosis is a disease of unknown aetiology. Little is known of the predictive factors of fibrosis. It has been suggested that PAI-1, uPA, TGF-β1, VEGF, IL-8, TNF-α influence this process. The aim of the study was to assess airway inflammatory and fibrosis markers in EBC in sarcoidosis and the effects of fibreoptic bronchoscopy (FOB), bronchoalveolar lavage fluid (BALF), transbronchial lung biopsy (TBLB) and bronchial mu- cosa membrane biopsy on their production in the airways. Material and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…Studies on sarcoidosis have shown that it is possible to identify inflammatory markers (e.g. TNF-alpha) in exhaled breath condensate using an enzyme immunoassay [16,17]. So the ability of the Aeonose™ to distinguish patients with sarcoidosis from healthy controls could (also) be due to the influence of inflammation [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on sarcoidosis have shown that it is possible to identify inflammatory markers (e.g. TNF-alpha) in exhaled breath condensate using an enzyme immunoassay [16,17]. So the ability of the Aeonose™ to distinguish patients with sarcoidosis from healthy controls could (also) be due to the influence of inflammation [18].…”
Section: Discussionmentioning
confidence: 99%
“…Another inflammatory marker that is supposed to play a role in the pathogenesis of both CRPS and sarcoidosis is TNF-alpha [6,9,10,15]. In patients with sarcoidosis TNF-alpha was found together with other inflammatory markers, IGF-1, PAI-1, TGF-beta1 and VEGF in exhaled breath condensate using an enzyme immunoassay [16,17]. This was followed by a study of Dragonieri et al who showed that an electronic nose was able to distinguish between sarcoidosis and healthy controls [18].…”
Section: Introductionmentioning
confidence: 99%
“…Collection and analysis of exhaled breath condensate (EBC) is a promising new approach in the diagnosis of lung diseases [1,2]. As a non-invasive and painless way of getting samples of lung liquid for detection of disease biomarkers, EBC attracts both researchers and medical practitioners because of the considerable advantages it offers over the rather painful and complicated bronchoalveolar lavage procedure [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Comparisons of the established technique of bronchoalveolar lavage (BAL) with EBC show little correlation between biomarkers in other diseases, with total protein levels being higher in BAL than EBC, but the dilution of BAL with the lavage fluid, and suction causing airway bleeding all contribute to make the results difficult to interpret [7]. Nevertheless, cytokines, chemokines, growth factors and markers of oxidative stress have been detected in the EBC of patients with sarcoidosis [4,[8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%